LEARNING METHODS OF ISLAMIC RELIGION AND CIVIL EDUCATION FOR THE FORMATION OF STUDENTS' ATTITUDE OF TOLERANCE AT SMP N 5 WATUMALANG WONOSOBO - Nikmiyati Nikmiyati; Noor Aziz; Muhammad Yusuf amin Nugroho (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2023)
One of the external factors that supports student success in learning is the learning method. Choosing the right method will greatly determine the success or failure of achieving learning objectives. This article was created with the aim of finding out 1) To find out the methods of learning religious education and character for students at SMP N 5 Watumalang. 2) To find out how tolerant students are at SMP Negeri 5 Watumalang. 3) To find out to what extent religious education and character learning methods contribute and tolerate students at SMP N 5 Watumalang. This research is qualitative research using observation, interviews and documentation in collecting data. Meanwhile, the data analysis uses inductive and deductive methods with a descriptive analytical approach, namely in the form of written or verbal data from sources and observations of learning activities, so that the author obtains a picture in accordance with the actual situation. The results of this research analysis are to find out that SMP Negeri 5 Watumalang has implemented Islamic religious education and morals in its learning process, and the factors that support and hinder the learning process of SMP Negeri 5 Watumalang. The results obtained from this research are that learning has been carried out at SMP Negeri 5 Watumalang since 2007, with an activity schedule starting at 07.15 - 14.15 every Monday to Saturday except Sundays which are closed. From the results of observations and interviews, data was also obtained regarding supporting factors in the learning process, including adequate facilities and infrastructure, quality of teachers, student activity in learning, and support from the community, especially student guardians. Meanwhile, inhibiting factors include varying student absorption capacity, lack of teacher discipline, and students' lack of concentration in learning.